Association between previous enterobiasis and current wheezing: Evaluation of 1018 children - AKKOÇ, TUNÇ (OCEAN SIDE PUBLICATIONS INC, 2007)
The aim of this study was to investigate the association between parasitosis and allergy. We surveyed all children aged 4-12 years living in poor hygienic conditions in a shantytown of Istanbul. After obtaining data from the International Study of Asthma and Allergies in Childhood (ISAAC) and an additional questionnaire, performing a skin-prick test (SPT), and determining total IgE, stool and perianal tape specimens were obtained from 1018 participating children. The prevalence of past episodes of wheezing, current wheezing, asthma, and rhinitis was 31, 14.6, 10.7, and 26.2%, respectively. Parasitosis was present in 49.1%, Enterobius vermicularis (23.3%), being the most common. A history of treatment for enterobiasis was present in 37%. Comparison of children with and without current enterobiasis revealed no significant difference in allergic manifestations and SPT results, except for serum total IgE level (p = 0.018), whereas children with previous enterobiasis were more likely to have current wheezing (p = 0.012). Current wheezers were more likely to have previous enterobiasis (p = 0.01) and a higher maternal employment level (p = 0.036) when compared with those without. According to logistic regression analysis, covariables significantly positively related with current wheezing were previous enterobiasis (p = 0.003) and being : 5 years of age (p = 0.043), whereas being the first child of the family (p = 0.043) was negatively related. A previous infection with E. vermicularis was found to potentiate current wheezing in a population living in a shantytown in Istanbul.
Keywords: allergy; asthma; children; Enterobius vermicularis; helminth infection; intestinal; ISAAC; parasitosis; risk factor; wheezing; PARASITE-SPECIFIC ANERGY; ALLERGIC REACTIVITY; HELMINTHIC INFECTION; TROPICAL ENVIRONMENT; SLUM CHILDREN; ANTHELMINTIC TREATMENT; HYGIENE HYPOTHESIS; CHILDHOOD ASTHMA; CYTOKINE CONTROL; SCHOOL-CHILDREN